Chemical profiling of polyphenolics in Eucalyptus globulus and evaluation of its hepato-renal protective potential against cyclophosphamide induced toxicity in mice - Ghareeb, Mosad Ahmed; Sobeh, Mansour; Wink, Michael (Antioxidants, 2019)
Cyclophosphamide (CP) is a potent anti-neoplastic and immunosuppressive agent; however, it causes multi-organ toxicity. We elucidated the protective activities of Eucalyptus globulus (EG) leaf extract against CP-induced hepato–renal toxicity. Mice were treated with EG for 15 days plus CP on day 12 and 13 of the experiment. Using HPLC-DAD-ESI-MS/MS, 26 secondary metabolites were identified in EG leaf extract. Out of them, 4 polyphenolic compounds were isolated: (1) 4-(O-β-d-xylopyranosyloxy)-3,5-di-hydroxy-benzoic acid, (2) 4-(O-α-l-rhamnopyranosyloxy)-3,5-di-hydroxy-benzoic acid, (3) gallic acid, and (4) methyl gallate. Effects of EG extract on biochemical parameters, gene expression, and immune-histopathological changes were assessed in comparison to mesna positive control. Results showed that EG improved CP-increased serum ALT, AST, creatinine, and blood urea nitrogen levels. The hepatic and renal tissue levels of MDA, nitric oxide, protein carbonyl, TNF-α, IL-6, and immunohistochemical expression of nuclear factor kappa-B (NF-kB) and caspase-3 were reduced. Also, hepatic and renal GSH contents, and nuclear factor E2-related factor 2 (NRf2)/ hemoxygenase-1 (HO-1) signaling levels were increased. Histopathological findings supported our findings where hepatic and renal architecture were almost restored. Results revealed the protective effects of EG against CP-induced hepato–renal toxicity. These effects may be related to EG antioxidant, anti-inflammatory, and anti-apoptotic properties coupled with activation of Nrf2/HO-1 signaling.
Gesehen am 31.10.2019